1999
DOI: 10.1080/089419399272539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Barriers of Oxidized Regenerated Cellulose (ORC) on Cecal and Sidewall Adhesions in the Presence and Absence of Bleeding

Abstract: Adhesion formation after bowel surgery is a significant problem. The objective of this study was to evaluate two adhesion barriers composed of oxidized regenerated cellulose (ORC) in a model of bowel surgery, with and without bleeding. Ceca of female New Zealand White rabbits were abraded with gauze and a 3 x 5 cm patch of peritoneum and underlying muscle was excised from the right sidewall. Animals were randomized to receive no treatment, INTERCEED Barrier (Ethicon, Inc.), or neutralized INTERCEED (nTC7). ORC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…However, made of oxidized cellulose, it is considered as xenobiotics and has low biocompatibility and low adhesiveness to tissues. Furthermore, when bleeding is not com pletely controlled at the applied site, its efficacy is lowered [9,10]. Accordingly, it is necessary to develop a tissue adhesion barrier that has enhanced safety, flexibility, and adhesiveness to tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, made of oxidized cellulose, it is considered as xenobiotics and has low biocompatibility and low adhesiveness to tissues. Furthermore, when bleeding is not com pletely controlled at the applied site, its efficacy is lowered [9,10]. Accordingly, it is necessary to develop a tissue adhesion barrier that has enhanced safety, flexibility, and adhesiveness to tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The representative antiadhesive agents are Interceed (Ethicon, Somerville, NJ, USA) [8-10], which was synthesized from ORC; Seprafilm (Genzyme Co., Cambridge, MA, USA) [9,10] crosslinked HA and CMC; and Surgiwrap (Mast Biosurgery, San Diego, CA, USA) [11,12] using Poly (lactic acid).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidized regenerating cellulose (Interceed®, Ethicon, Sommerville, NJ) is the only adhesion barrier that was proven to increase pregnancy rate in an RCT [23]. However, oxidized regenerating cellulose has limitations because it is difficult to handle laparoscopically and can cause adverse adhesiogenic effects in the presence of blood [24, 25]. Studies evaluating the efficacy of adhesion barriers in reducing the number of ASBO and enterotomies are rare.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several physical barriers are approved and available on the market as adhesion reduction agents. Nevertheless, their success in safety, costs and effectiveness vary [18,20,21,22,23,24,25]. A recent study revealed the results of 10-year follow-up after Hartmann’s procedure and the use of Seprafilm.…”
Section: Discussionmentioning
confidence: 99%